Diagnostic difficulties in esophageal atresia with proximal and distal tracheoesophageal fistula: a case report - Ezer, Semire Serin; Oğuzkurt, Pelin; Temiz, Abdülkerim; Ince, Emine; Hiçsönmez, Akgün (The Turkish Journal of Pediatrics, 2010)
The authors report two patients with esophageal atresia and double fistula, one of whom was diagnosed intraoperatively and the other preoperatively through upper pouch contrast study. Patients with proximal and distal fistula do not present with excessive oral secretion and drooling because they can swallow the saliva/meals that reach the trachea from the proximal esophagus via the proximal fistula and then from the trachea to the distal esophagus via the distal fistula. Thus, since this clinical entity can be easily overlooked, some radiological and clinical signs that are helpful for preoperative and intraoperative diagnosis of a proximal fistula are discussed.